A model of Learning Organization and its application in higher education centers - Khodayar Abili; Fatemeh Narenji Thani; کبری خباره; Ebrahim Mazari (Pizhūhish/hā-yi rahbarī va mudīriyyat-i āmūzishī, 2017)
This study aims to provide a learning organization SEM and the application of done at Tehran University. The research method is descriptive-correlational and analytical method was SEM. The population was University of Tehran staffs on the number of 2730 people. Sample size by using Cochran sampling formula and simple random sampling, were selected 243 people. To collect data, a questionnaire based on the model of Peter Senge (1990) designed by reliability (94/0 = α). Also evaluated and approved content and construct validity. For data analysis, Kolmogorov-Smirnov structural equation modeling, and one-sample t-test, was used. The results showed that the learning organization model has been fitted to the data. Accordingly, the individual features of the paradigm (γ =0/24) and systematic approach (γ =0/52) been effective. Systematic approach to the common cause (β=0/51) and collective learning (β=0/44) and shared vision have also had an impact on collective learning (β=0/17) has had impact. Finally, mental models based on shared vision and collective learning as well as individual features common cause whatsoever. The results showed that the application of learning organization and all aspects of its application in the target population, below the average and only mental patterns was middle.